Influence of an anti-tumor necrosis factor monoclonal antibody on cytokine levels in patients with sepsis. The CB0006 Sepsis Syndrome Study Group. - Fisher, C; Opal, S; Dhainaut, J; Stephens, S; Zimmerman, J; Nightingale, P; Harris, S; Schein, R; Panacek, E; Vincent, J (1993)
OBJECTIVES: To determine the safety, pharmacokinetics, and activity of an anti-tumor necrosis factor (TNF)-alpha monoclonal antibody in severe sepsis. DESIGN: Open-label, prospective, phase II multicenter trial with escalating doses of a murine monoclonal antibody (CB0006). SETTING: Twelve academic medical center intensive care units in the United States and Europe. PATIENTS: Eighty patients with severe sepsis or septic shock who received standard supportive care and antimicrobial therapy in addition to the anti-TNF antibody. INTERVENTIONS: Patients were treated intravenously with one of four dosing regimens with CB0006: 0.1 mg/kg, 1.0 mg/kg, 10 mg/kg or two doses of 1 mg/kg 24 hrs apart. MEASUREMENTS AND MAIN RESULTS: The murine monoclonal anti-TNF antibody was well tolerated despite the development of anti-murine antibodies in 98% of patients. No survival benefit was found for the total study population, but patients with increased circulating TNF concentrations at study entry appeared to benefit by the high dose anti-TNF antibody treatment. Increased interleukin (IL)-6 levels predicted a fatal outcome (p = .003), but TNF levels were not found to be a prognostic indicator. TNF levels were higher (206.7 +/- 60.7 vs. 85.9 +/- 26.1 pg/mL; p < .001) and outcome was poor (41% vs. 71% survival; p = .007) in patients who were in shock at study entry when compared with septic patients not in shock. CONCLUSIONS: The murine anti-TNF-alpha monoclonal antibody CB0006 has proven to be safe in this clinical trial and may prove to be useful in septic patients with increased circulating TNF concentrations. Further studies are needed to determine efficacy and the ultimate clinical utility of this immunotherapeutic agent in sepsis.